PENGARUH eWOM TERHADAP NIAT BERKUNJUNG WISATAWAN MELALUI ATTITUDE, SUBJECTIVE NORMS, DAN PERCEIVED BEHAVIOR CONTROL - Jiwandono, Deigo Jiwandono; Kusumawati, Andriani; Sunarti, Sunarti (FIA UB, 2020)
This study aims to examine the effect of eWOM on intention to visit through attitude, subjective norms and perceived behavioral control. In this paper the method used is the study of literature, which is done by collecting and analyzing various journals related to the research topic. After conducting a literature study, it is known that eWOM has a significant influence on perceived attitudes, subjective norms, behavioral control. Then attitudes, subjective norms, perceived behavioral control have a significant influence on the intention to visit. The practical implication of this study is that with eWOM information, tourism service providers can use eWOM as a tools for promoting their service products, as well as a tools to evaluate the service products they have. So that in the future, tourism service providers can provide better services to maintain and increase the number of tourists visiting.